GIS based Land Use Suitability of Diversified Cropping Systems in Bareli Watershed - Ingle, Sagar N.; Nagaraju, M. S. S.; Gadge, Priya S.; Deshmukh, D. P.; Dange, N. R. (International Journal of Economic Plants, 2021)
A study was undertaken to evaluate the soils in Bareli watershed, Seoni district of Madhya Pradesh for sustainable land use planning. Five soil series namely, Diwartola, Diwara, Bareli-1, Bareli-2 and Bareli-3 were tentatively identified and mapped into twenty-four mapping units and a soil map was generated using remote sensing and Geographic Information System (GIS) techniques. The land information generated during soil survey has been used to evaluate land capability, land irrigability, soil productivity and soil-site suitability for some medicinal, aromatic and spices crops. The soils were grouped into land capability sub-classes IVs and IVst and land irrigability sub-classes 2st, 3s, 3st and 4st. Soils of Diwartola, Bareli-1 and Bareli-3 were average and soils of Diwara and Bareli-2 were poor in soil productivity based on limitations of erosion, drainage and physicochemical properties. Soil-site suitability assessment reveals that soils of Bareli-1 were moderately suitable (S2) for cultivation of medicinal and spices crops like Ashwagandha, Mucana, Davana, Lemongrass, Turmeric and Ginger with moderate limitations of effective depth and slope, while, soils of Diwartola and Bareli-3 were marginally suitable (S3) for cultivation of these crops.